Bio-based substances from urban waste as auxiliaries for solar photo-Fenton treatment under mild conditions: optimization of operational variables - Gomis, J. (2015)
The use of soluble bio-based organic substances (SBO) obtained from urban wastes to expand the pH region where the photo-Fenton process can be applied has been investigated in this study. For this purpose, a mixture of six pollutants, namely acetaminophen, carbamazepine, amoxicillin, acetamiprid, clofibric acid and caffeine, at an initial concentration of 5 mg L−1 each, has been employed. Surface response methodology, based on the Doehlert matrix, has shown to be a useful tool to determine the effect of pH (in the range 3–7), concentration of SBO (15–25 mg L−1) and iron (2–6 mg L−1) on the performance of the photodegradation of the studied pollutants, measured by their half-life. Results indicate that, at high SBO concentration, the optimum pH shifts in most cases to a higher value (between 3 and 4) and that a significant loss of efficiency of the process was only observed at pH values above 5. An iron concentration of 4–5 mg L−1 and an amount of SBO of 19–22 mg L−1 have been determined to be the optimal conditions for the degradation of most of the studied pollutants at pH = 5.